Pendampingan Pembentukan English Study Club untuk Meningkatkan Motivasi Berbicara Bahasa Inggris pada Santri PPMH - Moh. Farid Maftuh; Jannatul Laily Noviabahari; A’thi Fauzani Wisudawati; Halim Ahmad Faizin; Aulia El Hakim; Pramudya Bagus Aji Wiranata (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The Community Service Program at the Miftahul Huda Islamic Boarding School (PPMH) in Doho Village, Dolopo District, Madiun Regency, is a solution to problems that occur in the community, especially among teenage students. Based on field observations and informal interviews conducted by the team with several students, they complained about their low motivation in speaking English. They feel a lack of confidence and their knowledge is still at a basic and immature level. Therefore, this activity is a program that will carry out mentoring training for the formation of an English Study Club to increase the motivation of PPMH Doho Dolopo Madiun students. Very basic things will be taught to them starting from providing basic training on small organizational management for students, increasing student motivation and abilities, fostering a collaborative and creative learning culture at the Islamic boarding school. The goal of this activity is to form an English Study Club as an English learning community. The implementation method is through direct training and mentoring to form the organizational structure of the English study club and run the organization properly. The results include improved soft skills competency, a more conducive learning environment, improved English language skills and motivation, particularly among students speaking English, and improved student managerial skills in running an English Study Club within the Islamic boarding school.